Low-cost physicochemical treatment for removal of ammonia, phosphate and nitrate contaminants from landfill leachate. Issue 12 (15th October 2019) - Morris, Sinead; Garcia-Cabellos, Guiomar; Ryan, David; Enright, Deirdre; Enright, Anne-Marie
Abstract: Four low-cost materials, oyster shells, pumice stone, sand and zeolite were employed as adsorbents in an adsorption batch assays investigating the removal of ammonia, phosphate and nitrate from an aqueous solution. These compounds were chosen as they represent typical compounds found in landfill leachate (LFL). Assay performance was evaluated by the Langmuir and Freundlich adsorption isotherms. The top two materials, oyster shells and pumice stone, were employed as adsorbents in a fixed-bed column trial examining the effect of bed height and flow rate on the treatment of a synthetic LFL. The trial concluded that the highest rates of adsorption were achieved using bed heights of 20 cm with a flow rate of 5 mL min −1 . After optimization, the system was employed for the treatment of LFL from Powerstown landfill, Carlow, Ireland. Ammonia and nitrate were effectively removed by both adsorption materials resulting in a reduction of influent ammonia and nitrate concentrations to below the national discharge limits set for these compounds of ≤4 mg L −1 and ≤50 mg L −1, respectively. In contrast, although similar high removal efficiencies were observed for phosphate, these rates were not maintained during the test period with overall results indicating reduced phosphate adsorption in comparison to the other compounds tested.